Etika Interaksi Sosial dalam Pola Meminta Izin Memasuki Rumah Perspektif Hadis - Agusta Putra, Yandri (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2024)
The moral decline that has occurred in the current era of globalization has caused concern in the community. The absence of etiquette when entering other people's homes, the absence of asking permission to enter the house, the absence of prior notification is often found in this day and age. This is contrary to the teachings of Shari'ah, which principle is that Adab is above knowledge. It is better for someone to be civilized but have little knowledge than someone who has a lot of knowledge but is not civilized. Basically, there cannot be any Shari'a demands unless there must be something bad behind it all that must be abandoned. Islam does not only demand knowledge, but must instill Adab first. Surely this is a problem of the people that must be addressed immediately. The purpose of this study is to provide a detailed description of the Prophet's explanation of what procedures / ethics must be considered in entering someone else's house in order to avoid disputes or protect the disgrace of the homeowner. This research collects data through a qualitative approach in the form of a literature review which includes articles, journals, theses, and books. The result of this research is to provide an understanding and emphasis on the importance of the ethics of asking permission in terms of visiting other people's homes. The conclusion of this study also implies that parents should instill good manners from an early age to children, especially the manners of visiting other people's homes.